Precipitation structure during various phases the life cycle of precipitating cloud systems using geostationary satellite and space-based precipitation radar over Peru - Kumar, S. (2020)
The life cycle of clouds consists of mainly into three phases, namely developing, mature, and dissipating phases. The information about the vertical structure of the precipitation during different phases of development will improve their representation in the cloud models. Whether specific regimes over Peru favor the formation or decay of the cloud systems and how their intensity varies during different phases of development will provide the insight into the precipitation structure over Peru. We used two satellite-based data, namely from Global Precipitation Measurement dual Precipitation Radar (GPM-DPR) and GOES (Geostationary Operational Environmental Satellite) to expose the vertical structure of precipitation during different phases of the precipitating cloud systems (PCSs). A PCS is defined using the GPM based near surface rainfall data and then GOES-based brightness temperature (BT) is used to identify a specific phase of PCS. In particular 9 hours of BT (e.g., time series of BT) data for a GPM DPR overpass is used to a specific phase of PCS. Once, all the PCSs are identified into a specific phase, their statistical properties are studied. The highest convective fraction area (~26%) and near surface rain rate (RR; 4.97 mm hr?1) are observed in developing phase of PCSs. Also, the convective fraction area and near surface RR decreases as cloud matures, and, least convective fraction area and RR (~4.11 mm hr?1) are observed in dissipating phase PCSs. The vertical structure of precipitation consists of more complex relation among different phases of PCSs. The vertical distributors of hydrometeors (e.g., radar reflectivity, RR, and DSD parameters) during various phases have different characteristics above and below the freezing height (~5 km). For example, convective precipitation has small concentration of higher sized hydrometeors below the freezing height, whereas mature has PCSs show different behavior. The total amount of water analysis shows that liquid and ice water amount varies during different phases and affect the rainfall characteristics. It is observed that precipitation characteristics during different phases are influenced by the Andes Mountain and developing phase PCSs have higher sized of hydrometeors with higher near surface RR at the north-eastern continent of Peru. © 2020 Informa UK Limited, trading as Taylor & Francis Group.